XPS Monitoring of Calcarenite Building Walls Long Exposed Outdoors: Estimation of Deterioration Trend from the Time Sequence of Curve-Fitted Spectra and PCA Exploration of the Large Dataset - Maria A. Acquavia; Francesco Cardellicchio; Mariangela Curcio; Fausto Langerame; Anna M. Salvi; Laura Scrano; Carmen Tesoro (Applied Sciences)
A temporal monitoring of monumental buildings in calcarenite, exposed outdoors in the considered Mediterranean environment of Southern Italy, was performed using XPS, the surface-specific technique. The methodology adopted to monitor the surfaces interacting with atmospheric agents and biotic/abiotic pollutants involved progressive sampling, extended to about five years, from the walls of a new building, specifically installed in the immediate vicinity of an ancient farmhouse in an advanced state of degradation. Taking the ancient building as the final temporal reference, the aim was to obtain adequate information on the degradation processes of calcarenitic stones, from the initial and evolving phases of the new building towards those representative of the old reference. A large set of XPS data was obtained by resolving, through curve-fitting, the acquired spectra into component peaks, identified as ‘indicator’ chemical groups, which trend as a function of time, supported by PCA, demonstrates a close compositional similarity between the samples of the new building analyzed after 52 months from its installation and those of the ancient building dating back to over a century ago. The results obtained can be considered in the diagnostic strategy of the ongoing PNRR programs dedicated to the care of historical monuments and ecosystem sustainability.